Kepemimpinan Pendidikan Islam (Konsep, Peran, dan Implementasinya di Lembaga Pendidikan Islam) - Misrawani, Misrawani; Refnawati, Refnawati; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to find out the concept, role and implementation of leadership in Islamic educational institutions. This study uses a library research method to examine the concept, role, and implementation of leadership in Islamic educational institutions. Data were collected through a literature review that included Islamic leadership theory, leadership models in Islamic education, and factors that affect the effectiveness of leadership in Islamic educational institutions. The analysis is carried out with a qualitative descriptive approach, where the results of the literature review are systematically arranged to provide a comprehensive understanding. The results of the analysis show that leadership is a person who has the ability, artistic power to influence, aspire, and direct the behavior of a person or group/organization (motivating individuals without any element of coercion) in their work by means of obedience, trust, honor, and enthusiastic cooperation in achieving common goals. Educational leadership is the way or effort of school leaders in influencing, encouraging, guiding, directing and mobilizing teachers, staff, students, parents of students and other related parties to work or participate in order to achieve the goals that have been set. Educational leaders must master the concept of leadership, education, in order to achieve educational goals optimally, effectively, and efficiently, who are responsible and understand their main tasks and functions